Chemical compounds emitted by main components used in interior of vehicles - W. Librelon; J. C. Souza; V. F. C. Lins (eXPRESS Polymer Letters)
Odors from materials used in new vehicles may cause satisfaction or dissatisfaction for people. This duality is due to a stimulation caused by receptors which act differently in each individual. It is already known that odors exhaling in a vehicles interior are caused by a gaseous mixture of the various materials which are volatilized, especially with the increase of internal temperature. The components of a newly manufactured automotive vehicles interior of high surface representativeness selected in this work are eight: air conditioner, ceiling liner, shelf package, rubber mats, door panel, carpet, instrument panel, and seats, which were analyzed by gas chromatography for the identification of volatile substances. The proportion of the peak area of each compound was calculated. Gas chromatography analysis identified the main substances from materials used in interior of vehicles which contribute to the new car odor: toluene, p-xylene, ethylbenzene or benzene derivatives, except in carcass of air conditioner. Polypropylene is a constituent of these components, except the rubber mats. Carbon disulfide appeared with a significant proportion of area in rubber mats and contributed in the formation of car odors.